4 - Rethinking the Role of Universities in Africa: Leadership as a Missing Link in Explaining University Performance in Uganda - Roberts Kabeba Muriisa (Journal of Higher Education in Africa, 2014)
The subject of this paper is the place of leadership in redefining the role of the university in Africa in general and Uganda in particular. The ‘African University’ today, like any other university, has clear mandates and roles; research, teaching and community service, clearly laid down on paper in many of the universities’ manuals and strategic plans. But, in reality, these roles are not performed at all or are performed in a manner that may not warrant clear roles. Increasingly, it is observed that less quality teaching, less research, and less community service are being done. This situation calls for rethinking what role should universities play. While many expla- nations have been offered for the declining performance of the university, in this paper I contend that leadership plays a significant role not only in influencing escalation of crises but also in averting them, especially in Ugandan universities. The paper answers mainly three research questions: (i) How do changes and transitions taking place in the university sector affect the role of universities in Uganda? (ii) How does leadership respond to the challenges faced by universities? and (iii) What are the challenges faced by leadership and how do these challenges influence their response to university challenges? Using different documents, and basing on the behaviour approaches to study organisations the study makes an analysis of the role of leadership in the functioning of the university. The paper concludes faced with many challenges, universities have changed course and focus and that they need rethinking their roles. It is concluded that the role of leadership has been overlooked yet they occupy a central role in the performance of the university.